Podcasts in teaching ESL - Chaikovska, Olha (Professional Pedagogics, 2018)
The paper reports on research into the integration of podcasts in ESL teaching. This issue is currently of great interest. The article aims to highlight the potential of podcasts in teaching English. The study investigates this issue  by comparing and generalizing the existing theoretical material  on the topic and examining the effects of podcast application in language learning. The study is concerned with basic characteristics and types of podcasts. Much attention is given to general and professional podcasts, veterinarian and agricultural authentic listening material, in particular. The review of most popular English language podcasts for general and professional usage is given in the study. The author analyzes the strategies for podcast integration in ESL teaching process. It is found that both types of podcasts can be used with the first year university students: general podcasts can be used at preparatory cycle of curriculum, while profession podcasts can be integrated into profession- focused cycle of curriculum. The primary concern of this research is to examine the advantages of integration the podcasts in ESL classroom. The author argues that podcasts could serve as one of the up-to-date effective strategies for ESL learning. It can be concluded that authenticity, multilevelness, ability to promote intrinsic motivation and personal growth, effectiveness (the combination of visual and sound information) and convenience of podcasts make them attractive tool in language learning.
Keywords: ESL; podcasts; professionally-based; characteristics; authentic; flexibility; motivation; effectiveness; up-to-date